Perkembangan Perusahaan Taksi Blue Bird sebagai Penyedia Jasa Transportasi Massal di Indonesia (1970-2015) - Nadyana Dwi Qoriah Perwani; Umasih Umasih; Abrar Abrar (Universitas Negeri Makassar, 2022)
This study’s purpose is to explain the development of Blue Bird taxi company as the provider of mass transportation service in Indonesia between the years of 1970-2015. The research method used in this research is the history method, which consists of heuristic, verification, interpretation, and historiography. In the heuristic phase, the researcher gathered research resources from primary sources such as a book titled Sang Burung Biru, as well as newspapers that were published during the same era. The researcher also gathered writing resources from secondary sources, such as libraries’ annual reports, as well as books that are related to either transportations or companies. The result of this research shows that the Blue Bird taxi company illegally existed within the 1960s. Then, in 1972, the Blue Bird taxi officially operated in the roads of Jakarta until today.